Forming active recombinant enterokinase expressed in Escherichia coli - Thi Thu Hong, Le; Kim Phuong, Luong; Thi Thu Hien, Trinh; Thi Mai Phuong, Nguyen; Nam Hai, Truong; Thi Huyen, Do (Vietnam Journal of Biotechnology, 2020)
Enterokinase is a serine protease commonly used in some biotechnology researches. For these purposes, the light chain containing enterokinase activity has usually been expressed as recombinant protein in different expression systems because natural enterokinase extraction is often ineffective. In this study, we examined the formation of recombinant enterokinase expressed in Escherichia coli with biological activity. The thioredoxin-enterokinase (trx-ent) fusion protein was autocleavaged into thioredoxin and enterokinase when expressed under insoluble form, denatured with guanidine and then refolded with suitable oxidation and reduction steps. Meanwhile, soluble expression as well as insoluble form denatured by urea had not enzymatic activity. Denaturant solution of 6 M guanidine along with the re-folding conditions in oxidized glutathione oxidation buffers followed by the reduced glutathione buffer with arginine was applied to produce trx-ent protein capable of self-cleavage. The recombinant light-chain enterokinase protein had a size of about 35 kDa on the Tris-glycine gel. Initial assessment on substance had shown that enterokinase was capable of cleaving thioredoxin-sumoprotease into thioredoxin and sumoprotease. This result provides the base for the production of active recombinant enterokinase to be used in recombinant protein expression technology.